Self-Association of Purified Reconstituted ER Luminal Spacer Climp63 - Zhao, Jinghua; Hu, Junjie (Frontiers in Cell and Developmental Biology, 2020)
Membranes of the endoplasmic reticulum (ER) are shaped into cisternal sheets and cylindrical tubules. How ER sheets are generated and maintained is not clear. ER membrane protein Climp63 is enriched in sheets and routinely used as a marker of this structure. The luminal domain (LD) of Climp63 is predicted to be highly helical, and it may form bridges between parallel membranes, regulating the abundance and width of ER sheets. Here, we purified the LD and full-length (FL) Climp63 to analyze their homotypic interactions. The N-terminal tagged LD self-associated up to trimers in solution, but was extremely aggregation-prone when the GST tag was removed. Purified FL Climp63 formed detectable but moderate interactions with both the FL protein and the LD. When Climp63 was reconstituted into proteoliposomes with its LD facing out, the homotypic interactions were retained and could be competed by soluble LD, though vesicle clustering was not observed. These results demonstrate a direct self-association of Climp63, supporting its role as an ER luminal spacer.